Relationships between pulsating auroras and field-aligned electric currents - Fujii, Ryoichi; Oguti, Takasi; Yamamoto, Tatsundo (1985)
P(論文) On the basis of ground-based all-sky TV images of auroras and simultaneous data of magnetic fluctuations observed by MAGSAT, the relationships between pulsating auroras and field-aligned currents are examined. It is found that pulsating auroras are embedded in the southernmost region of the upward field-aligned currents, and that E-W component fluctuations of magnetic field at MAGSAT are related well to fluctuations in auroral luminosities along a trajectory of the magnetic foot point of MAGSAT at the altitude of 100km. The period of fluctuations is about 5s and the spatial extent of the pulsation corresponds to 40km in horizontal size in one of the examples. Although the separation of temporal variations from spatial structures is not yet made, the good relationships between auroral and magnetic fluctuations indicate that pulsating auroral patches are accompanied by field-aligned pair currents relevant to each pulsating auroral patch. departmental bulletin paper